A Systematization of Micro-Mobility Safety in Sustainable Cities - Kędzior-Laskowska, Małgorzata (Olsztyn Economic Journal, 2024)
The purpose of this analysis was to introduce the safety category to the general context of micromobility development in modern cities. The article is theoretical and is intended to introduce the safety category in micromobility. It focuses on the relatively young and attractive micromobility market in terms of greening socio-economic activities and development. The micromobility market is receiving increasing attention from both citizens and city planners. The safety category was determined by: a) various internationally differentiated technical vehicle standards, b) micromobility users road accidents, c) cities transport infrastructure, and d) personal data of micromobility users. It was demonstrated that safety is an important issue in transport and city planning. The micromobility vehicles hold high significance in promoting sustainable development. Therefore, it is imperative to incorporate micromobility into sustainable urban mobility plans and incentivize individuals to change their mobility patterns. However, there is a need to observe the market because it is rather dynamic and more and more vehicles appear, also for elderly and people with physical disabilities. The emergence of novel technologies and vehicles has the potential to transform cities, thereby ensuring their safety and fostering a friendly environment for their citizens.